Effect of somatic cell count on dairy products: a review - Talukder, Mukta; Ahmed, HM Manir (Asian Journal of Medical and Biological Research, 2017)
Somatic cells are the most essential factors naturally present in milk, and somatic cell count (SCC) is used as an indicator of monitoring mastitis incidence in the herd and also to assess the quality of milk. In addition, SCC is frequently used to determine quality payments to dairy producers. The SCC is directly related to get maximum milk production from individual cow and a lower SCC indicates better animal health, as somatic cells originate only from inside the animal's udder. SCC monitoring is important because as the number of somatic cells increases, milk yield is likely to fall, primarily due to the damage to milk-producing tissue in the udder caused by mastitis pathogens and the toxins they produce, particularly when epithelial cells are lost. Keeping low SSC will allow good quality more raw milk and provide a better product to milk processors whether used as fluid milk or converted to milk based products. Somatic cells containing lipolytic and proteolytic enzymes lead to degrade major nutrients fats and proteins, respectively. Elevated SCC is related to udder inflammation, which leads to alter the normal microbial count and physicochemical parameters of milk, as well as the quality of heat treated fluid milk and milk based product. The objective of this review is to discuss on the SSC and endogenous enzymes released from somatic cells in raw milk as well as effect of somatic cells count and their endogenous enzymes in processed milk and milk based products. Asian J. Med. Biol. Res. March 2017, 3(1): 1-9